Experimental investigation of the strength of glass fiber-reinforced concrete exposed to high temperature - Amir Hamzeh Keykha (Mechanics of Advanced Composite Structures)
This study investigated the effects of high temperature exposure on the compressive, tensile, and flexural strengths of concrete containing glass fiber. A total of 108 cubic specimens (150 mm × 150 mm × 150 mm), cylindrical specimens (300 mm × 150 mm), and prismatic specimens (500 mm × 150 mm × 150 mm) were prepared for compressive, tensile, and flexural strength testing, respectively. The specimens were incorporated with 1%, 2%, and 3% glass fiber and cured for 28 days to derive the desired strengths. The specimens were then annealed and subjected to experiments in which they were exposed to high temperature (600°C) for 30 minutes, one hour, and two hours. The specimens were cooled via slow cooling (exposure to air) and fast cooling (water spraying immediately after exposure to heat). Results showed that the presence of glass fiber exerted different effects on specimen strength and that heat caused the formation of numerous cracks in the specimens.